THE EFFECT OF AI INTEGRATION IN HR PRACTICES ON EMPLOYEE PERFORMANCE: MEDIATING ROLES OF ENGAGEMENT AND PERCEIVED JOB SECURITY - Usman, Osly; Suryadi, Suryadi; Sari, Rindi Nurlaila (Bina Bangsa International Journal of Business and Management, 2025)
This study examines the effect of Artificial Intelligence (AI) implementation in Human Resource Management (HRM) on employee performance, with employee engagement and perceived job security as mediating variables. This research was conducted in a biopharmaceutical company in Jakarta with 100 respondents. The method used for data collection is a survey with data collection techniques through online questionnaires. The data processing technique used is Structural Equation Modeling (SEM) with Partial Least Squares (PLS). The results showed that the application of AI in HR has a significant influence on employee engagement, perceived job security, and employee performance. In addition, perceived job security was found to mediate the relationship between AI implementation and employee performance, while employee engagement did not play a mediating role on employee performance. The practical implications of this study provide a reference for HR managers and policy makers to effectively implement AI technologies, support innovation, and maintain employee well-being.